NUMERICAL APPROACH OF THE BLADE SHAPE AND NUMBER ON THE PERFORMANCE OF MULTIPLE BLADE CLOSED TYPE IMPULSE WIND TURBINE - Sasongko, Herman; Mirmanto, Heru; Bangga, Galih; Nugrahani, Elita Fidiya; Pasaribu, Johan Nicholas (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
An impulse turbine uses drag force on its blades to produce torque on its rotor. As fluid flows over the blades, pressure changes occur at the nozzle, which increases the fluid's velocity and reduces the static pressure at the nozzle outlet. The high-momentum fluid then impinges on the rotor blades, generating frictional force and resulting in torque production. To study the impact of blade shape and number on the turbine's performance, simulations were conducted. The results indicate that blades with an angle of 0° and 180° are optimal for creating high-pressure vortices on the concave surface of the blade. Addition-ally, more blades always result in higher torque and power out-put by increasing the active area of the blades. However, in the case of blades with an angle of 0° and 180°, 8 blades produced more torque than 12 blades with an angle of 0° and 90°. There-fore, blades with an angle of 0° and 180° are highly effective at generating drag force and producing torque.